NAVIGATING ECOLOGICAL NARRATIVES OF THE ANTHROPOCENE IN KIM SCOTT’S THAT DEADMAN DANCE - Phukan, Abhilasha; Doley, Dipak Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In the discourse of the Anthropocene, Scott’s literary works have emerged as a prominent voice critiquing the current epoch characterized by degrading impact of colonisation on the environment. Scott deviates from the conventional storytelling by connecting personal narratives with broader ecological themes, urging the readers to reconsider the colonial histories and its impact in the human and non-human lives of Australia. Through elaborate depictions of altered landscapes and after effects of colonisations, his narratives explore the relationship with the humans and the ecological sytems. This paper attempts to explore the ecological narratives of the Anthropocene as depicted in Scott’s novel That Deadman Dance and also attempts to explore on the socio- political legacies of colonialism and capitalism that blurs the lines between history and fiction. This paper shall consider a re-reading of the novel from an ecological perspective that shall enable readers to engage deeply with the environmental narratives and reflect on the material consequences of colonialism. The methodology which is adopted for the study is qualitative in nature supported by data gathered from primary and secondary sources.